(untitled) (World Bulletin of Management and Law, 2024)
In this article, when exploiting oil and gas fields, a specific exploitation system for oil fields with gas caps is required. The initial reservoir pressures in them should be slightly lower than the saturation pressure. As a result, only part of the gas dissolves in the oil, and the remaining part is located on top of the oil, forming the primary gas cap, which is the effect of gas production from the gas cap on the oil production rate and the importance of controlling the displacement state of the gas-oil contact surfaces.